Expression of stem cell biomarker aldehyde dehydrogenase 1 (ALDH1) in canine mammary tumor - GAVHANE, D S; SINGH, A; SOOD, N K; GUPTA, K (The Indian Journal of Animal Sciences, 2016)
The study was conducted to investigate the immunohistochemical expression of a stem cell biomarker, ALDH1 in CMTs. ALDH1 is a cytosolic enzyme responsible for oxidizing intracellular aldehydes leading to the oxidation of retinol to retinoic acid, a key step involved in early stem cell differentiation. It was noticed that the cells expressing this marker possess ability to self renew. In present investigation, we assessed the expression of ALDH1 by immunohistochemistry on paraffin embedded tissue sections from 31 confirmed clinical cases of canine mammary tumors (CMT). The results of immunohistochemistry were analyzed semiquantitatively by calculating percentage score and staining intensity using light microscope and comparing it with the histological types. ALDH1 expression was detected in 26 (83%) of CMTs and it was observed in benign lesions, invasive cells and cells undergoing epithelial to mesenchymal transition (EMT). The high expression patterns of ALDH1 in various histological types of CMT indicated poor prognosis.